2020
DOI: 10.1002/gj.3958
|View full text |Cite
|
Sign up to set email alerts
|

Origin of Late Jurassichigh‐Kfelsic volcanic rocks and related Au mineralization in the Dongyang deposit, central‐eastern Fujian,SEChina, and its tectonic implications

Abstract: The newly discovered Dongyang low‐sulphidation epithermal Au deposit is located in central‐eastern Fujian Province, coastal SE China. Ore bodies occur in Late Jurassic rhyolite porphyry, rhyolite, and dacitic crystal tuff lava. In this study, rhyolite and dacitic crystal tuff lava are dated to 151.9 ± 0.4 Ma and 158.3 ± 0.4 Ma, respectively, and belong to the second member of the Nanyuan Formation. They are high in K2O (6.91–3.81 wt%) and Na2O/K2O (0.55–0.02), strongly peraluminous (A/CNK = 2.11–1.67) and high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 88 publications
(168 reference statements)
0
3
0
Order By: Relevance
“…As Figure 2 shows, the Xinghua Bay Offshore Wind Farm is a prominent offshore wind energy farm in this marine area, comprising 59 turbines with a combined installed capacity of 357.4 megawatts [33]. Tuff from the second member of the Jurassic Nanyuan formation (J 3 n b ) is widely found in this marine area [34], so it is selected and processed as rock samples for this study.…”
Section: Preparation Of Rock Samplesmentioning
confidence: 99%
“…As Figure 2 shows, the Xinghua Bay Offshore Wind Farm is a prominent offshore wind energy farm in this marine area, comprising 59 turbines with a combined installed capacity of 357.4 megawatts [33]. Tuff from the second member of the Jurassic Nanyuan formation (J 3 n b ) is widely found in this marine area [34], so it is selected and processed as rock samples for this study.…”
Section: Preparation Of Rock Samplesmentioning
confidence: 99%
“…Some notable regions include Shanghang in the southwest, Jianning in the northwest, Zhenghe-Jian'ou in the north, and Dehua-Youxi-Yongtai in the central-eastern part of the province, all of which have yielded large polymetallic deposits [6][7][8]. The Dehua-Youxi-Yongtai region is commonly referred to as the "Golden Triangle" exploration area, where significant gold mines, such as Ancun, Qiucun, and Shuangqishan, have been discovered [9][10][11][12]. Several scholars have conducted research using geological chronology, fluid inclusion data, and isotope dating, and concluded that the metals in this area originate from magmatic hydrothermal sources [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, together with the widespread Early Jurassic granitoids in the Great Xing'an, Lesser Xing'an, and Zhangguangcai Ranges (W. C. Ge, Wu, Zhou, & Zhang, 2005;Han et al, 2019;F. Y. Wu, Sun, Jahn, & Wilde, 2004;Z. Xu, Yang, et al, 2020;Z.…”
mentioning
confidence: 99%